2011
DOI: 10.1007/s00442-011-2152-4
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of secondary succession rates across temperate latitudes of the Eastern USA: climate, soils, and species pools

Abstract: Climate change is widely expected to induce large shifts in the geographic distribution of plant communities, but early successional ecosystems may be less sensitive to broad-scale climatic trends because they are driven by interactions between species that are only indirectly related to temperature and rainfall. Building on a biogeographic analysis of secondary succession rates across the Eastern Deciduous Forest (EDF) of North America, we describe an experimental study designed to quantify the relative exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 17 publications
2
19
1
Order By: Relevance
“…). The same factors may influence the rate of succession towards the climax, which may vary geographically (Fridley & Wright ). Despite these limitations, it is practical to consider an endpoint to which succession proceeds, and on a time scale of a few centuries we can consider an endpoint that changes relatively little, especially in its dominant species (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). The same factors may influence the rate of succession towards the climax, which may vary geographically (Fridley & Wright ). Despite these limitations, it is practical to consider an endpoint to which succession proceeds, and on a time scale of a few centuries we can consider an endpoint that changes relatively little, especially in its dominant species (cf.…”
Section: Introductionmentioning
confidence: 99%
“…; Wright & Fridley ; Prévosto et al. ; Fridley & Wright ). The use of different sampling methods makes cross‐study comparisons difficult (Prach & Řehounková ).…”
Section: Introductionmentioning
confidence: 99%
“…These treatments consisted of a gradient of four soil textures (100% topsoil; 75:25 topsoil: sand; 50:50 topsoil: sand; and 25:75 topsoil: sand), representing the range in soil texture and fertility observed across the latitudinal gradient (Fridley and Wright, 2012). Topsoil was sourced from local commercial sources, due to transportation limitations, and so there were site differences in macro‐ and micronutrient availability.…”
Section: Methodsmentioning
confidence: 99%
“…The vegetation treatments were chosen to emulate two stages in old‐field succession and included native plants present along the latitudinal gradient (Fridley and Wright, 2012). Bunchgrasses were started from locally collected seed in a greenhouse and then shipped as plugs to all sites.…”
Section: Methodsmentioning
confidence: 99%
“…According to Wright and Fridley (2010), fields of the Northeast may favour herbaceous persistence due to more fertile soils, cooler temperatures and early successional species pools. Fridley and Wright (2012) concluded that early successional ecosystems may be less sensitive to broad-scale climatic trends because they are driven by interactions between species that are only indirectly related to temperature and rainfall. According to their results, seedlings of southern woody pioneer species are better able to quickly establish in fields after abandonment, regardless of climate regime.…”
Section: Woody Encroachmentmentioning
confidence: 99%